CRISPR/Cas9-mediated knockout of PsLykX gene of pea (Pisum sativum L.) leads to loss of symbiotic nodules - Igor Yu. Zhuravlev; Anton A. Lyakhovets; Andrew G. Matveenko; Maria A. Lebedeva; Aleksandr I. Zhernakov; Veronika Y. Simonova; Anton S. Sulima; Igor A. Tikhonovich; Vladimir A. Zhukov (Transgenic Research, 2026)

Lateral Root versus Nodule: The Auxin-Cytokinin Interplay - Mahboobeh Azarakhsh; Maria A. Lebedeva (Journal of Plant Growth Regulation, 2023)

Compositional evolution of igneous garnets: calcic garnets from alkaline rocks of Terskiy Coast (Kola Alkaline Carbonatite Province) - Alexey A. Vozniak; Maya G. Kopylova; Anna A. Nosova; Liudmila V. Sazonova; Natalia M. Lebedeva; Maria V. Stifeeva (Mineralogy and Petrology, 2023)

Valorization of beetle infected spruce to produce textile fibers and biofuels: Environmental sustainability evaluated by life cycle assessment - Kuntawit Witthayolankowit; Alessandro Marson; Kiran Reddy Baddigam; Daria Lebedeva; Manzoorahmed Shaikh; Anuja Kane; Deepika Gupta; Maria Ivarsson Wide; Aji P. Mathew; David Kubička; Alessandro Manzardo; Joseph S.M. Samec (Chemical Engineering Journal, 2023)

Overexpression of Parkin in the Neuronal Progenitor Cells from a Patient with Parkinson’s Disease Shifts the Transcriptome Towards the Normal State - Olga Lebedeva; Daniil Poberezhniy; Ekaterina Novosadova; Tatiana Gerasimova; Lyudmila Novosadova; Elena Arsenyeva; Ekaterina Stepanenko; Darya Shimchenko; Egor Volovikov; Ksenia Anufrieva; Sergey Illarioshkin; Maria Lagarkova; et al. (Molecular Neurobiology, 2023)

Climate and socio‐economic factors explain differences between observed and expected naturalization patterns of European plants around the world - Robin Pouteau; Wilfried Thuiller; Carsten Hobohm; Caroline Brunel; Barry J. Conn; Wayne Dawson; Michele de Sá Dechoum; Aleksandr L. Ebel; Franz Essl; Ori Fragman‐Sapir; Trevor Fristoe; Nejc Jogan; et al. (Global Ecology and Biogeography, 2021)
Aim The number of naturalized (i.e. established) alien species has increased rapidly over recent centuries. Given the differences in environmental tolerances among species, little is known about what factors determine the extent to which the observed size of the naturalized range of a species and hence the extent to which the observed richness of naturalized species of a region approach their full potential. Here, we asked which region‐ and species‐specific characteristics explain differences between observed and expected naturalizations. Location Global. Time period Present. Major taxa studied Vascular plants. Methods We determined the observed naturalized distribution outside Europe for 1,485 species endemic to Europe using the Global Naturalized Alien Flora (GloNAF) database and their expected distributions outside Europe using species distribution models. First, we investigated which of seven socio‐economic factors related to introduction pathways, anthropogenic pressures and inventory effort best explained the differences between observed and expected naturalized European floras. Second, we examined whether distributional features, economic use and functional traits explain the extent to which species have filled their expected ranges outside Europe. Results In terms of suitable area, more than 95% of expected naturalizations of European plants were not yet observed. Species were naturalized in only 4.2% of their suitable regions outside of Europe (range filling) and in 0.4% of their unsuitable regions (range expansion). Anthropogenic habitat disturbance primarily explained the difference between observed and expected naturalized European floras, as did the number of treaties relevant to invasive species. Species of ornamental and economic value and with large specific leaf area performed better at filling and expanding beyond their expected range. Main conclusions The naturalization of alien plant species is explained by climate matching but also by the regional level of human development, the introduction pressure associated with the ornamental and economic values of the species and their adaptation to disturbed environments.

Plant tumors: a hundred years of study - Irina E. Dodueva; Maria A. Lebedeva; Kseniya A. Kuznetsova; Maria S. Gancheva; Svetlana S. Paponova; Ludmila L. Lutova (Planta, 2020)

A comparison of bioclimatic potential in two global regions during the late twentieth century and early twenty-first century - Maria G. Lebedeva; Anthony R. Lupo; Chasity B. Henson; Alexandr B. Solovyov; Yury G. Chendev; Patrick S. Market (International Journal of Biometeorology, 2018)